2018
DOI: 10.1128/jmbe.v19i2.1460
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Stand-Alone Online Learning Module for Cellular Respiration Instruction

Abstract: With the recent rise of alternative instructional methodologies such as flipped classrooms and active learning, many core concepts are being introduced outside of the classroom prior to scheduled class meeting times. One popular means for external concept introduction in many undergraduate biology courses is the use of stand-alone online learning modules. Using a group of four large introductory biology course sections, we investigate the use of a stand-alone online learning module developed using animations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…This aligns with studies showing that assignment of formative assessments improves learning for students from multiple institutional types (Freeman et al, 2011;Orr and Foster, 2013;Pape-Lindstrom et al, 2018). Goff et al (2018) demonstrated learning gains from supplementing lectures with a different online learning module on cellular respiration. Importantly, our results also show that a single instructional intervention (i.e., an online tutorial) is unable to guide all students to provide completely Scientific explanations.…”
Section: Implications For Educatorssupporting
confidence: 85%
See 2 more Smart Citations
“…This aligns with studies showing that assignment of formative assessments improves learning for students from multiple institutional types (Freeman et al, 2011;Orr and Foster, 2013;Pape-Lindstrom et al, 2018). Goff et al (2018) demonstrated learning gains from supplementing lectures with a different online learning module on cellular respiration. Importantly, our results also show that a single instructional intervention (i.e., an online tutorial) is unable to guide all students to provide completely Scientific explanations.…”
Section: Implications For Educatorssupporting
confidence: 85%
“…, 2018 ). Goff et al. (2018) demonstrated learning gains from supplementing lectures with a different online learning module on cellular respiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quasi-experimental and mixed-methods studies that were included in the review evaluated various learning modules in different disciplines. Significant improvement in knowledge was reported in all studies (Boet et al, 2017;Elkin et al, 2018;Ens et al, 2017;Gagnon et al, 2015;Goff et al, 2018;Kennedy et al, 2019;Parsons et al, 2019;Rafferty et al, 2019). An evaluation of nursing students using an online self-directed module on scientific literature demonstrated an improved knowledge for all the modules except for one that was considered to be most challenging (Gagnon et al, 2015).…”
Section: Knowledge Acquisitionmentioning
confidence: 80%
“…Fifteen of the 20 studies reported an improvement in knowledge as a result of self-directed learning modules (Boet et al, 2017; da Costa Vieira et al, 2017; Elkin et al, 2018; Ens et al, 2017; Gagnon et al, 2015; Gillan et al, 2018; Goff et al, 2018; Karvinen et al, 2017; Kennedy et al, 2019; McCutcheon et al, 2015; Parsons et al, 2019; Rafferty et al, 2019; Rahmati et al, 2018; Warner et al, 2020; Wu et al, 2018). Five randomized studies designed creative ways to enhance the effectiveness of online modules (da Costa Vieira et al, 2017; Gillan et al, 2018; Karvinen et al, 2017; Rahmati et al, 2018; Warner et al, 2020).…”
Section: Resultsmentioning
confidence: 99%